The King of the Dwarves: a new cryptic species of Dainty Frog (Anura: Pyxicephalidae: Cacosternum) from the eastern Great Escarpment of South Africa - Conradie, Werner (Zootaxa, 2014)
Phylogenetic reconstruction using the mitochondrial 16S marker shows the presence of a cryptic species of Cacosternum (Anura: Pyxicephalidae) from the eastern Great Escarpment of South Africa, supporting the Greater Maputaland-Pondoland-Albany region of vertebrate endemism. Bioacoustic and morphological characteristics, in conjunction with colouration differences, allow the description of this cryptic species. Tadpoles and details of life history are described.